Manufacture of 3D Compact Graphene Oxide Macrostructures - Siyu Liu (Advanced Materials Interfaces)
Abstract Graphene oxide (GO) is an important candidate material in the 2D‐material family. A single GO nanosheet comprises a one‐atom‐thick graphene sheet with oxygen‐containing functional groups. The interaction of oxygen groups on GO can help assemble GO nanosheets into macroscopic structures as flat membranes or nonplanar 3D structures. The manufacturing of 3D GO‐based macrostructures is of great interest as many applications require nonplanar structures, but current reviews on fabricating 3D GO‐based macrostructures with compact morphology are limited. This article reviews available methods to manufacture 3D GO‐based compact macrostructures, including molding, origami and kirigami, stimuli‐responsive deformation, and 3D printing. With these methods, the manufactured 3D structures have compact layered morphology under scanning electron microscopy. The compact morphology makes the GO‐based structures achieve high mechanical stiffness and strength to satisfy applications that need excellent mechanical properties. These methods have their advantages and drawbacks, so it is needed to select them carefully for specific applications. The development of processing methods to manufacture 3D macrostructures will enable GO‐based materials to achieve wide real‐life applications.